KOMUNIKASI POLITIK PEREMPUAN - Nur Ainiyah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2017)
This research has been aim for showing about how discourse analysis in media pilkada politic communication in situbondo, politic communication strategic was built byÂ  candidate of regency fatayat inhegemoni or power of priyayi politic in Situbondo. So became development in politic communication of candidate leader of area on practice and scholarship. Then many questions will be answered are: 1) how is Fatayat of women Situbondo preception of realty politic in Situbondo. 2) How do Fatayat women face the obstacles of political communication in Situbondo? 3) How do Fatayat women build political communication strategies in dealing with kyai political hegemony in Situbondo? By using qualitative-explorative research approach, some steps in observation data collection procedure, interview and documentation are done consistently and continuously so that the first research produce political climate in Situbondo is in the power of kyai (men) in gender analysis is patriarchy political culture so space women's politics are not as free as the political space of men. Both communication barriers and women's political participation are found in several factors, including cultural barriers, political capital constraints and human resource constraints. The three strategies of women's political communication are carried out in several ways: firstly lobbying, establishing cooperation with various parties and agencies, both communication processes ranging from message selection, media selection and proper selection of communication so that communication strategy becomes effective.